Barriers that impede the implementation of circular economy practices for the automotive industry: The conceptual framework - Yahaya, Siti Norbaya; Bakar, Mohd Hafiz; Ahmad Murad, Murzidah; Mohd Yusof, Nur Shaziera Aqma; Ghazali, Aziatul Waznah (International Information and Engineering Technology Association, 2024)
Researchers and practitioners have been paying close attention to the circular economy (CE) since it addresses both social and environmental benefits. It allows for the optimization of the manufacturing process by developing sustainable products that retain as much of their value as feasible. This study focuses on the constraints that obstruct the application of circular economy practices in the Malaysian automobile industry. Slight attention has been paid in the literature to the hurdles to CE adoption in Malaysia. Moreover, the pandemic COVID- 19 that disrupted the supply chain in automotive industries are the foundation of issue that led to this study. Governmental, economic, and social barriers are identified among the barriers that impede the implementation of CE for automotive industry in Malaysia. Expected result will suggest the most significant variable influencing barriers to the implementation of CE practices. Researchers might use the proposed new conceptual framework to conduct future research or add more variables to the study.